Metabolite profiling reveals the interaction of chitin-glucan with the gut microbiota. Issue 1 (9th November 2020) - Rodriguez, Julie; Neyrinck, Audrey M.; Zhang, Zhengxiao; Seethaler, Benjamin; Nazare, Julie-Anne; Robles Sánchez, Cándido; Roumain, Martin; Muccioli, Giulio G.; Bindels, Laure B.; Cani, Patrice D.; Maquet, Véronique; Laville, Martine; et al.
ABSTRACT: Dietary fibers are considered beneficial nutrients for health. Current data suggest that their interaction with the gut microbiota largely contributes to their physiological effects. In this context, chitin-glucan (CG) improves metabolic disorders associated with obesity in mice, but its effect on gut microbiota has never been evaluated in humans. This study explores the effect of a 3-week intervention with CG supplementation in healthy individuals on gut microbiota composition and bacterial metabolites. CG was given to healthy volunteers (n = 15) for three weeks as a supplement (4.5 g/day). Food diary, visual analog and Bristol stool form scales and a "quality of life" survey were analyzed. Among gut microbiota-derived metabolites, bile acids (BA), long- and short-chain fatty acids (LCFA, SCFA) profiling were assessed in stool samples. The gut microbiota (primary outcome) was analyzed by Illumina sequencing. A 3-week supplementation with CG is well tolerated in healthy humans. CG induces specific changes in the gut microbiota composition, with Eubacterium, Dorea and Roseburia genera showing the strongest regulation. In addition, CG increased bacterial metabolites in feces including butyric, iso-valeric, caproic and vaccenic acids. No major changes were observed for the fecal BA profile following CG intervention. In summary, our work reveals new potential bacterial genera and gut microbiota-derived metabolites characterizing the interaction between an insoluble dietary fiber -CG- and the gut microbiota. Graphical abstract: